Development and Validation of a Nomogram for Predicting Prognosis to Immune Checkpoint Inhibitors Plus Chemotherapy in Patients With Non-Small Cell Lung Cancer - Zeng, Hao; Huang, Wei-wei; Liu, Yu-jie; Huang, Qin; Zhao, Sheng-min; Li, Ya-lun; Tian, Pan-wen; Li, Wei-min (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitors (ICIs) plus chemotherapy improved the prognosis of patients with non-small cell lung cancer (NSCLC); however, reliable prognostic biomarkers are lacking. We explored factors associated with prognosis and developed a predictive model. Methods: We retrospectively analyzed 130 consecutive stage IIIA-IVB NSCLC patients treated with ICIs combined with chemotherapy. COX univariate and multivariate proportional hazards regression analyses were used to identify prognostic factors associated with progression-free survival (PFS). A nomogram was developed based on key factors in the training cohort (n=86) and evaluated in the validation cohort (n=44). According to the nomogram-based total point scores, we divided patients into low- and high-risk groups. Results: In the training cohort, bone metastasis (P=0.017) and an increased derived neutrophil-to-lymphocyte ratio (P=0.018) were significantly associated with poor PFS, while smoking (P=0.007) and programmed death-ligand 1 (PD-L1) ≥ 50% (P=0.001) were associated with improved PFS. A nomogram based on these factors was developed to predict PFS at 3, 6 and 12 months. The C-index of the nomogram to predict PFS was 0.725 (95% CI: 0.711-0.739) in the training cohort and 0.688 (95% CI: 0.665-0.711) in the validation cohort. The area under the curve (AUC) exhibited an acceptable discriminative ability, and calibration curves demonstrated a consistency between the actual results and predictions. In the training cohort, the median PFS (mPFS) was 12.3 and 5.7 months in the low- and high-risk groups, respectively (P<0.001). In the validation cohort, the mPFS was 12.6 and 6.2 months in the low- and high-risk groups, respectively (P=0.021). Conclusions: A predictive nomogram was developed and internally validated to help clinicians assess prognosis early for advanced NSCLC patients who received ICI plus chemotherapy.